REGIONAL DIFFERENCES IN HEALTH IN SPAIN - AN EMPIRICAL ANALYSIS - David Cantarero; Marta Pascual (European Regional Science Association (ERSA), 2005)
In this paper we report an analysis of income related health inequalities at the regional level in Spain. We use among others the self assessed health measure and explain the observed differences across Spanish regions due to the effect of socioeconomic characteristics. New data from the Spanish National Health Survey have been used. The results have important implications for health policies and provide empirical evidence about the relationship between health and socioeconomic factors in Spain which should affect the decisions about health care financing system.
Keywords: 330